WITHOUT CHALK AND WITH DANCE: THE USE OF TIK TOK FOR COMPLEMENTARY EDUCATION BEYOND THE CLASSROOM (Comunicação & Inovação, 2024)
The inclusion of new pedagogical practices that include the languages ​​of information and communication technologies is an emerging need in contemporary times. The transformation of ways of learning is demanding that teachers also change the way of teaching. In this context, this article analyzes strategies used by six Brazilian teachers on the social networking platform TikTok. As a methodology, we used the VDA (Video Data Analysis) described by Nassauer and Legewie (2021). The results pointed to innovations and a great engagement of the audience in the contents that used strategies different from the traditional ones in the classroom.
Keywords: Education; Social Media; TikTok; Teaching; Communication